Daily adjustment of glucocorticoids by patients with adrenal insufficiency - Schöfl, Christof; Mayr, Bernhard; Maison, Nicole; Beuschlein, Felix; Meyer, Gesine; Badenhoop, Klaus; Kienitz, Tina; Quinkler, Marcus (Clinical Endocrinology, 2019)
Background: Patients with adrenal insufficiency (AI) require lifelong glucocorticoid (GC) replacement. AI patients need to adjust GC dosage in response to stressful events and illness in order to prevent life-threatening adrenal crisis (AC). Aim: To evaluate self-management of patients with AI. Methods: Four German centres, which are using patient's diary as part of their routine clinical practice, instructed AI patients to prospectively document any discomfort, intercurrent illness or stressful events as well as changes in GC therapy on a daily basis. Diaries of 80 patients (44 females, 52.9 ± 15.9 years, 34 primary AI) were collected and analysed. A symptom score sheet was used to evaluate severity of discomfort. Results: In total, 34 074 patient days (93.4 years) were recorded. 4622 days with discomfort were documented. On 35% of those days (n = 1621), patients increased their GC dose (4.8% of all days). Patients who recorded discomfort had a median of four episodes of discomfort, which lasted a median of 2 days. Women documented significantly more episodes of discomfort than men (P = 0.014). Low-to-median symptom scores resulted in GC increase by 50%-60%, whereas high symptom scores and/or fever resulted in doubling GC daily dose. However, dose increase was only 55% in situations indicating gastrointestinal (GI) infection. Conclusion: Severe discomfort did not always result in dose increase, especially in GI infection. However, low symptom scores resulted in an inappropriate GC increase in some patients. This underscores an urgent need for improved training methods. Keeping daily records might be a useful tool for continued and individualized patient education.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Addison's disease; adrenal crisis; hydrocortisone; patient's diary